Lethal Dose of Calcium Bentonite in Wistar Rats - Dwika Audiyananda; Hendro Sudjono Yuwono; Adria Adnan (Althea Medical Journal, 2021)
Background: Calcium bentonite is a type of clay produced by a devitrification of volcanic ash which is often used as a traditional medicine to absorb toxins and waste products of metabolism. The aim of this study was to determine the lethal dose of calcium bentonite in Wistar rats to explore its toxicity level and safe use.Methods: Fifty male and female Wistar rats were randomly divided into five groups for each sex. The control group was given 5 cc aquadest whereas the other four groups received calcium bentonite solution of 50 mg/kgBW, 300 mg/kgBW, 2,000 mg/kgBW, and 5,000 mg/kgBW, respectively, at a single dose. The weight was observed for up to 7 days and analyzed using the unpaired t-test and Mann-Whitney test. The death rate was calculated using the probit analysis. Median lethal dose results were then classified according to Loomis Criteria. Results: No deaths occurred at the highest dose, suggesting that the median lethal dose value of calcium bentonite was >5,000 mg/kgBW. No weight loss occurred due to the administration of calcium bentonite and a significant increase in the body weight was even observed in the male rat group. Interestingly, a significant decrease was found in the female rats group when compared to the control group.Conclusions: Calcium bentonite is classified as a practically non-toxic material with a median lethal dose of over 5,000 mg/kgBW.